Investigate the electromagnetic waves to desalinate gulf water and beyond - Elmutasim, Imadeldin Elsayed; Mohamed, Izzeldin I. (IEEE, 2020)
In recent times, modeling in electromagnetic field has drawn much attention due to revolutionize the world in wide technology aspects. According to that, promising increases daily to achieve the life requirements and mitigate the challenges such as water lack. A whole the world rely on water which consider the backbone of the life to sustain the life and development. Gulf countries are among the most arid environments of the world due to the shortage of natural water resource as well as rainfall. Consequently, the countries in the region totally depends on the Gulf water desalination process, which is consider a heavy duty to the governments due to high cost and complicated processing. This paper takes into account the matter via focus in electromagnetic filed to model the gulf salt water and give technical proposal with respect to chemical elements utilizing Geometric Cylindrical Black Tank GCBT to exploit the resources in gulf region. The proposal depends on exposed the salt water to the electromagnetic field to increase conductivity and raise the oxygen solubility as well as boost the rainfall capability through evaporation process. The study which is considered Qatar parameters and the similar countries would open the door to different fabrication processes such salt industry and derivatives together with mitigate the influences of the desalination. This work result emphasized the strong correlation between the electromagnetic field, wavelength and salinity level in various regions. Overall the proposal considers the gulf water electromagnetically and how to accommodate in desalination, underwater creatures and link over the sea.